Korelasi volume prostat terhadap derajat lower urinary tract symptoms - Jufriady Ismy; Sarah Safira; Iskandar Zakaria (DiscoverSys Inc., 2020)
Introduction: Benign prostatic hyperplasia is a health problem whose incidence ranks second highest in the field of urology. One of the cause is the more severe the complaint that arises is the heavier prostat volume which can cause the iritative and obstructive symptoms or better known as lower urinary tract symptoms(LUTS) which will be assessed based of international prostate symptoms score (IPSS). This study aims to determine prostate volume correlation with lower urinary tract symptoms severity in RSUD dr. Zainoel Abidin Banda Aceh. Knowledge of the volume of the prostate is important in management of patients with benign prostatic hyperplasia.Method: This study uses the Cross Sectional design by selecting respondents in accidental sampling with a total of 31 patient. The data obtained were then analyzed by the Spearman test.Result: The univariat data shows that 18 patient (58.1%)Â are in Grade III (31-50 cc) and the most coming patient have LUTS scoring symptoms level on moderate (8-19) are 12 patient (38.7%) and severe symptoms (20-35) are 17 patient (54.8%). The results of prostate volume with lower urinary tract symptoms data analysis show that the p-value = 0.323 (p>0.05).Conclusion: The results of this study indicate that the prostate volume doesnâ€™t have correlation with lower urinary tract symptoms severity in patient with benign prostatic hyperplasia in RSUD dr. Zainoel Abidin Banda Aceh.Â Latar Belakang: Benign prostatic hyperplasia (BPH) merupakan masalah kesehatan yang insidensinya menempati urutan kedua tertinggi di bidang urologi. Salah satu penyebab semakin beratnya keluhan yang muncul adalah semakin besarnya volume prostat dan dapat menyebabkan gejala klinis berupa gejala iritatif dan obstruktif atau lebih dikenal dengan lower urinary tract symptoms (LUTS) yang akan dinilai berdasarkan international prostate symptoms score (IPSS). Metode: Penelitian ini bertujuan untuk mengetahui korelasi volume prostat dengan derajat lower urinary tract symptoms di RSUD dr. Zainoel Abidin Banda Aceh. Pengetahuan tentang volume prostat sangat penting dalam menangani pasien-pasien dengan benign prostatic hyperplasia. Studi ini menggunakan desain Cross Sectional dengan memilih responden secara accidental sampling dengan jumlah sebanyak 31 pasien.Hasil: Data yang didapat kemudian dianalisis dengan uji Spearman. Hasil analisis data univariat menunjukkan bahwa 18 orang pasien (58,1%) memiliki volume prostat Grade III (31-50 cc) dan paling banyak pasien yang memiliki skor derajat LUTS sedang (8-19) yaitu sebanyak 12 pasien (38,7%) dan derajat LUTS berat (20-35) sebanyak 17 pasien (54,8%). Hasil analisis data volume prostat dengan derajat LUTS menunjukkan bahwa nilai p-value = 0,323 (p>0,05).Simpulan: Hasil penelitian ini menunjukkan bahwa volume prostat tidak memiliki korelasi dengan derajat LUTS pasien BPH di RSUD dr. Zainoel Abidin Banda Aceh.